The Gene Ontology Annotation (GOA) Project: Implementation of GO in SWISS-PROT, TrEMBL, and InterPro - Camon, Evelyn; Magrane, Michele; Barrell, Daniel; Binns, David; Fleischmann, Wolfgang; Kersey, Paul; Mulder, Nicola; Oinn, Tom; Maslen, John; Cox, Anthony; Apweiler, Rolf

(untitled) (Genome Research, 2003)
Gene Ontology Annotation (GOA) is a project run by the European Bioinformatics Institute (EBI) that aims to provide assignments of terms from the Gene Ontology (GO) resource to gene products in a number of its databases (http://www.ebi.ac.uk/GOA). In the first stage of this project, GO assignments have been applied to a data set representing the complete human proteome by a combination of electronic mappings and manual curation. This vocabulary has also been applied to the nonredundant proteome sets for all other completely sequenced organisms as well as to proteins from a wide range of organisms where the proteome is not yet complete.